Drought can cause phytoplankton growth intensification in Barra Bonita reservoir - Watanabe, Fernanda [UNESP]; Rodrigues, Thanan [UNESP]; Bernardo, Nariane [UNESP]; Ntara, Enner Alca [UNESP]; Imai, Nilton [UNESP] (Springer, 2016)
In this research, we investigated the possible consequences of the 2012-2014 drought in Southeastern Brazil on growing phytoplankton in a eutrophic reservoir. Weather has direct influence to phytoplankton communities and, consequently, underwater light climate which drives important processes in aquatic systems. Absorption coefficient of phytoplankton pigment (a(phi)) and chlorophylla (Chl-a) concentration were determined in laboratory in order to analyze the interference of phytoplankton biomass over light. In addition, a historical monthly rainfall series in the reservoir was analyzed. Results showed clearly the strong drought effect over the monthly useful volume and flow rate. Both of them play important roles to water column mixing and retention time which increase the nutrients availability in the system and phytoplankton biomass. Chl-a concentration and aphy values were extremely high [maximum Chl-a of 797.8 mg m(-3) and a(phi)(440) of almost 6 m(-1) in October]. So, more attention should be paid to water quality in long episodes of drought as occurred from 2012 to 2014.
Keywords: Bio-optical status; Underwater light climate; Chlorophyll-a; Inland waters